Flywheel system with synchronous reluctance and permanent magnet generators - KHALIZADEH CLAUDE (2004)
The present invention provides a flywheel system with a variable speed synchronous reluctance motor-generator and a variable speed permanent magnet generator for providing backup power. The flywheel system incorporates rotating elements supported by electromagnetic bearings. Electric power provided by the backup generator maintains electromagnetic bearing operation during that portion of the coast down period when shaft speed falls below the minimum required for operation of the synchronous reluctance motor-generator.